EXTERNAL BREAST PROSTHESES IN POST-MASTECTOMY CARE IN GERMANY - WOMENʼS EXPERIENCES: A QUALITATIVE STUDY - Regina Wiedemann; Wilfried Schnepp (University of Ostrava, 2017)
Aim: In Germany, external breast prostheses are recognized and funded as medical devices for adjustment and care following a mastectomy due to breast cancer. Nonetheless, there is a lack of awareness of the prostheses-fitting service in German breast centres and outpatient care. In this study breast cancer survivors give voice to their experiences. Design: The study employs qualitative research evaluation methods. Methods: Data was collected via semi-structured interviews. The analysis was carried out via open and axial coding. Results: Women's experiences and requirements are presented in a two-phase model. Phase one describes their experiences of shock and crisis, and the subsequent initial prosthesis fitting in hospital. Phase two describes the womenʼs desire for normality, which they hope to achieve with the help of a breast prosthesis. Conclusion: The results confirm the consequences of losing a breast, the resulting distress, and the importance of a good-quality prosthesis for body image, femininity, and psychosocial well-being. The study confirms that a lack of information and choice in prosthesis fitting is a common problem. For the first time, the two-phase model demonstrates the differences between the initial hospital treatment and womenʼs long-term needs. Keywords: breast cancer, external breast prostheses, mastectomy, supportive care, qualitative research.